2018
DOI: 10.3386/w24970
|View full text |Cite
|
Sign up to set email alerts
|

Hazed and Confused: The Effect of Air Pollution on Dementia

Abstract: Tech and Yale. The views expressed herein are those of the authors and do not necessarily reflect the views of the National Bureau of Economic Research. NBER working papers are circulated for discussion and comment purposes. They have not been peerreviewed or been subject to the review by the NBER Board of Directors that accompanies official NBER publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
2
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 37 publications
1
62
2
3
Order By: Relevance
“…Our results with respect to associations between air pollution (from LUR models), NAD, PD, and AD were consistent with several previous studies. Large-scale multi-city studies in the United States found that for every 1 μg/m 3 increase in annual PM 2.5 , risk of NAD and PD increased by 1.3 to 8% [77,78], compared to our estimate of a 9% increase per an interquartile range increase in PM 2.5 of 1.5 μg/m 3 . A matched case-control study in Denmark found 9% risk increase in PD for one interquartile range increase (2.97 μg/m 3 ) in NO 2 [79], somewhat smaller than our estimate of a 12% increase for an interquartile range increase in NO 2 of ppb (~17 µg/m 3 ).…”
Section: Discussioncontrasting
confidence: 77%
“…Our results with respect to associations between air pollution (from LUR models), NAD, PD, and AD were consistent with several previous studies. Large-scale multi-city studies in the United States found that for every 1 μg/m 3 increase in annual PM 2.5 , risk of NAD and PD increased by 1.3 to 8% [77,78], compared to our estimate of a 9% increase per an interquartile range increase in PM 2.5 of 1.5 μg/m 3 . A matched case-control study in Denmark found 9% risk increase in PD for one interquartile range increase (2.97 μg/m 3 ) in NO 2 [79], somewhat smaller than our estimate of a 12% increase for an interquartile range increase in NO 2 of ppb (~17 µg/m 3 ).…”
Section: Discussioncontrasting
confidence: 77%
“…[5] Studies in the US and UK have focused on a dementia outcome derived from electronic health records, in Medicare and the Clinical Practice Research Database (CPRD). [8,9] The large scale Medicare study included 6.9 million older adults who were followed up for 55.4 million personyears of whom 23% were recorded as having developed dementia at some stage; this required the recording of dementia using an insurance claim code. [8] Investigators obtained ZIP+4 codes from Social Security records, corresponding to a single mail delivery segment (but not unique address) for the follow up period.…”
Section: The State Of the Literaturementioning
confidence: 99%
“…[8,9] The large scale Medicare study included 6.9 million older adults who were followed up for 55.4 million personyears of whom 23% were recorded as having developed dementia at some stage; this required the recording of dementia using an insurance claim code. [8] Investigators obtained ZIP+4 codes from Social Security records, corresponding to a single mail delivery segment (but not unique address) for the follow up period. The latitude and longitude of the centroid of each ZIP+4 code was derived and the square of the inverse distance to each air pollution monitor was used to calculate a weighted average of PM2.5 exposure for each location.…”
Section: The State Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…This damage function is an often monetized representation of the impacts the economy can suffer from changes in environmental conditions. In the case of air pollution, impacts take the form of increased mortality and morbidity (11)(12)(13), losses of work hours and reduced productivity (14), losses in human capital (15,16) and social capital (17), and decreased recreational value (18), among others. The main advantage of working with IAMs is the possibility they offer to researchers and policy makers to visualize the current state of the economy and test alternative environmental policies or scenarios.…”
Section: Iams Of Air Pollution Are One Of the Main Policy Tools Availmentioning
confidence: 99%